Rostrum system for automated height adjustment - Shahrul Faiz, Sabir Ahmad (2008)
Rostrum is a very important part of any ceremony especially a formal ceremony. It is used to attract attention of the ceremony to the speaker. It is also used to instil confidence in first time speakers. The rostrum is an international item for ceremonies yet most of it has a fixed height. As it is known, the international citizens have a variable average height which means the rostrum cannot have a fixed height. This project concentrates on producing a rostrum system for automated height adjustment. The height adjustment allows the speaker to speak comfortably without having to hunch or tiptoe. The system is controlled by a single PIC microcontroller and the driver to rotate the motor in two directions is used to protect the PIC from current feedback. The mechanism used in the rostrum is the lead screw method where the lead screw is attached or welded onto the motor and connected to the rostrum. The rotation clockwise and counter clockwise makes the rostrum move upwards and downwards. The body of the rostrum is made of Poly Methyl Methacrylate Acrylic to make it look unique and attract attention of audience. This rostrum can be used in all situation and functions as it is unique and still fulfils the basic function of the rostrum.